The Development of Nursing Care Model for Severe Multiple Injury in Krabi Hospital - กัญจนิตานนท์, จารุพักตร์; วิภวกานต์, สุชาตา; พรหมบุตร, รัตนา (Journal of The Royal Thai Army Nurses, 2019)
This research and development study aimed to develop nursing care model for severe multiple injury in krabi hospital. Sample consisted of 85 registered nurses using the nursing care model, And all 632 patients with severe multiple injury who were admitted to Krabi Hospital between June 1st, 2017 and September 30th, 2018. Tools used in the research implementation were: a medical records review form, a questionnaire about opinions towards using the nursing care model and practices and nurse ‘s satisfaction, a scorecard indicator for monitoring each patient’s quality of care. Data were analyzed using mean, percentage, standard deviation Independent t test and content analysis. The results of this study revealed as follows. 1. The situational analysis were no nursing care model for patient with severe multiple injury, the practice is based on the knowledge and experience of nurses. 2. The nursing care model for patient with severe multiple injury consisted of three phases: pre-hospital phase, in-hospital phase, definite care and continuing of care after discharge. 3. The nursing outcomes of implementing the nursing care model were: a) In emergency department: trauma patient level 1 (life threatening) less than 2 hours increased from 76.51% to 97.06 %, get blood within 30 minute increase from 69.56% to 88.75%, penetrating abdominal trauma with shock patient have surgery within 30 minute increase from 77.26% to 81.47, emergency craniotomy/craniectomy increase from 90.11% to 100%, reducing mortality of PS score > 0.75 from 9.52% to 4.04 and The registered nurse’s satisfaction towards using the nursing care model increased from 78.36 % to 85.68 All findings of this study suggest that the nursing care model for patients with severe multiple injury can be used for the safety of patients and preventing serious complications.